Mucosal Invariant T cells are Diminished in Very Early-Onset Inflammatory Bowel Disease. Issue 4 (October 2021) - Dou, Ying; Maurer, Kelly; Conrad, Maire; Patel, Trusha; Shraim, Rawan; Sullivan, Kathleen E.; Kelsen, Judith
ABSTRACT: Objectives: Very early-onset inflammatory bowel disease (VEO-IBD) arises in children less than 6 years old, a critical time for immunologic development and maturation of the intestinal microbiome. Non-conventional lymphocytes, defined here as mucosal-associated invariant T cells and innate lymphocytes, require microbial products for either development or expansion, aspects that could be altered in very early-onset inflammatory bowel disease. Our objective was to define conventional leukocyte and non-conventional lymphocyte populations in controls and patients using multiparameter flow cytometry to test the hypothesis that their frequencies would be altered in a chronic inflammatory state associated with significant dysbiosis. Methods: Multiparameter flow cytometry was used in a control cohort of 105 subjects to define age-effects, not previously comprehensively examined for these cell types in humans. Differences were defined between 263 unique age-matched patients with VEO-IBD and 105 controls using Student t -test. Subjects were divided into two age groups at the time of sampling to control for age-related changes in immune composition. Results: Intermediate monocytes were consistently decreased in patients with VEO-IBD compared to controls. Mucosal-associated invariant T cells were significantly lower in patients with long-standing disease. Levels were less than half of those seen in the age-matched control cohort. The innate lymphoid cells type 2 population was expanded in the youngest patients. Conclusion: Mucosal-associated invariant T cells are diminished years after presentation with inflammatory bowel disease. This durable effect of early life intestinal inflammation may have long-term consequences. Diminished mucosal-associated invariant T cells could impact host defense of intestinal infections. Abstract : Supplemental Digital Content is available in the text